PENGARUH MODEL PEMBELAJARAN VISUAL, AUDITORY, KINESTHETIC BERBANTUAN MULTIMEDIA BERBASIS PREZI TERHADAP HASIL BELAJAR MAHASISWA PADA MATA KULIAH PAJAK PERPAJAKAN - Edutivia Mardetini; Siti Fatimah; Dian Eka Amrina (Pendidikan Ekonomi FKIP Universitas Sriwijaya, in partnership with Asosiasi Profesi Pendidikan Ekonomi Indonesia (ASPROPENDO), 2019)
The purpose of this study is to prove the influence of Visual, Auditory, Kinesthetic- assisted multimedia learning models based on Prezi on student learning outcomes in tax tax subjects in FKIP Unsri Economic Education. This research is an experimental study using a Quasi Experimental Design research design in the form of Nonequivalent Control Group Design. The population in this study were all semester VII students who received tax and taxation subjects totaling 88 people. The sampling technique uses cluster random sampling, which is drawn so that Palembang campus students are obtained as an experimental class and the Indralaya campus as a control class. Data collection techniques used by the test. Analysis of test data by looking for improved student learning outcomes in the experimental class and control class with the formula n-gain. Hypothesis testing using non-parametric statistics, namely Kolmogorov Smirnov with the help of SPPS version 24 can be seen the value of Sig. 0,000 is smaller than @ 0.05, then Ho is rejected and Ha is accepted. Then it can be concluded that there is an influence of Visual, Auditory, Kinesthetic learning model assisted by multimedia based on Prezi on student learning outcomes in taxation tax subjects in FKIP Unsri Economic Education.